A comparative numerical study on natural convection in inclined wavy and flat-plate solar collectors - Varol, Yasin; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2008)
The present study deals with the numerical analysis of natural convection heat transfer inside the inclined solar collectors. Two collectors are compared. In the first case, the collector has wavy absorber and in the second case, it has flat absorber. The solution was performed assuming the isothermal boundary conditions of absorbers and covers of collectors. CFDRC commercial software is used to simulate the laminar flow and thermal field. Governing parameters are taken as Rayleigh number (from 1 x 10(6) to 5 x 10(7)), inclination angle (from 20 degrees to 60 degrees), wave length (from 1.33 to 4) and aspect ratio (from 0 to 4). Results are presented by streamlines, isotherms and local and mean Nusselt numbers. It is observed that flow and thermal fields are affected by the shape of enclosure and heat transfer rate increases in the case of wavy enclosure than that of flat enclosure. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: natural convection; solar collector; inclined enclosure; heat transfer